Pelatihan Jurnalistik Dasar di UPT SMA Negeri 3 Sinjai - Adeh Ijam Putri Utami; Nurhayani; Jumardi; Ramli, Satria; Faridah; Fajriani Azis (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
Journalism is the activity of dealing with news, news material, from coverage to proper preparation for transmission.  Journalism is defined as conveying messages to the public through organized means of communication.  The purpose of this community service is to improve self-quality, prepare students for the future and equip them with the ability to write news.  In the task of community service, an implementation method is determined that determines the criteria for inviting activity participants, forming journalistic understanding, and encouraging young people who have journalistic skills.  Journalism focuses on gathering news material, reporting events, writing news, editing news scripts, and presenting news through the media.  The element of news is the most important thing in the journalistic process.  In news, the most important element is 5w+1h.  The 5w+1h elements include what, who, when, where, why and how.  Basic journalism training can have a major impact on student education and the development of interests and skills in the world of journalism.  Students will also benefit from this activity, namely the opportunity to write news as an alternative profession in the future.  By doing this training, participants can improve their knowledge and skills in writing news and be able to communicate well.